The Effect of Oral Chitosan Supplementation on Leptin Levels and HOMA-IR in Male Wistar Rats (Rattus norvegicus) with an Obesity Model - Lidwina Stefani; I Made Pande Dwipayana; Ida Ayu Alit Widhiartini; Desak Made Wihandani; I Putu Bayu Mayura (Green Publisher Indonesia, 2025)
This study investigates the role of chitosan in modulating leptin and insulin levels, key hormones involved in metabolic disorders, and compares its effectiveness with orlistat, a commonly used anti-obesity drug. An experimental post-test only group design was used involving 20 healthy male Wistar rats aged 3–4 months. After a seven-day acclimation, obesity was induced through a high-fat, high-glucose diet. The rats were then divided into five groups: a positive control group (K+) receiving orlistat, a negative control (K−) receiving a standard diet, and three treatment groups receiving chitosan at 2.5% (P1), 5% (P2), and 7.5% (P3) concentrations, respectively, for 14 days. Leptin and HOMA-IR levels were measured via blood samples collected from the retro-orbital sinus. The Kruskal-Wallis test showed significant differences among groups (p<0.05). Mean leptin levels were highest in K− (5.10±0.35 ng/dL) and lowest in K+ (3.03±0.71 ng/dL), while P2 showed a notable reduction (3.71±0.32 ng/dL). HOMA-IR levels followed a similar trend, with the lowest in K+ (1.00±0.08) and significantly reduced in P2 (1.34±0.11) compared to K− (2.29±0.25). Post Hoc analysis confirmed that P2 had significantly better outcomes than K−, though not as effective as orlistat. In conclusion, chitosan—particularly at 5% concentration—can reduce leptin and HOMA-IR levels, improving insulin resistance in obesity, though orlistat remains more effective.